MANAGEMENT OF DEVELOPMENT OF RELIGIOUS MODERATION VALUES - Simangunsong, Arimbi Syahkila; Wijaya, Candra (International Journal of Cultural and Social Science, 2025)
This study seeks to elucidate the management of religious moderation values development within the school context, particularly at MTs Yapdi, utilizing a qualitative methodology. This study primarily concentrates on four managerial dimensions: planning, organizing, implementing, and supervising. The employed research method is a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The study's findings demonstrate that the planning for the cultivation of religious moderation values is executed through the integration of religious activities, including congregational Dhuha prayers and tausyiah, alongside reinforcement within the Pancasila Student Profile Strengthening Project (P5) initiatives. The organization is conducted by engaging various pertinent subjects, including PPKn, IPS, Akidah Akhlak, and Al-Qur'an Hadith, which embody values of tolerance, mutual respect, and appreciation of diversity. Activities are implemented using a contextual learning approach, both within and beyond the classroom, focusing on practical application in daily life. Supervision is conducted by evaluating students' attitudes and behaviors in the application of moderation values, rather than solely relying on academic metrics.